A new Hyblaeidae species from Solomon Islands. Studies of Hyblaeidae 4 (Insecta: Lepidoptera) - U. Buchsbaum; M.-Y. Chen (SHILAP, 2021)
The species Hyblaea solomonensis Buchsbaum & Chen, sp. n. is described from the Solomon Islands. The species is to be placed in the Hyblaea constellata Guenée, 1852 - species group due to its similarity in the external morphological features, as well as in the genital structures. The new species differs from all other species in this group.